Analisis Yuridis Tindak Pidana Infanticide Berdasarkan Putusan Pengadilan No. 3311/PID.B/2018/PN.SBY - Tjandra Wijaya; Farma Nihayatul Aliyah; Imam Wahyudi; Inang Fitnasari (PT FORMOSA CENDEKIA GLOBAL, 2022)
The infanticide crime is a special crime , in which one can do so is the biological mother of the infant. This specificity will be the core of this paper, reviewing the factors that cause the crime is done because it becomes the specificity of this criminal act. In addition to reviewing it , the writing of this paper will also be discuss about things that the judges consideration who hear case of infanticide murder, whether in the form of mitigating or incriminating reason. This research is conducted by empirical juridical who examine the crime according to reality in real life of society. The end of this study concluded that the main thing that causes a mother to kill her baby is the embarrassment factor, because it has given birth to achild outside a legal marriage